Prevention of postoperative pain in patients with hip joint pathology and obesity - S. A. Ardashev; I. F. Akhtyamov; Kh. Ch. Khan' (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Osteoarthritis today is one of the most important causes of disability and a decrease in the quality of life of older patients, which, as a rule, is due to the presence of restrictions on independent movement and self-care. Persistent pain syndrome, which is the leading manifestation of the disease, also significantly reduces the quality of life. The number of obese people is increasing every year, and so is the number of operations to replace joints with artificial ones due to the large impact of excess weight on the incidence of osteoarthritis. Objective - to evaluate the effectiveness of pain relief in overweight and obese patients who have undergone total primary hip replacement at 3.6, 12 months. and 5 years in comparison with patients with normal body weight. Materials and methods. A comparative study of 154 clinical observations was conducted using the VAS pain scale in the aspect of impaired weight characteristics of two groups of patients. Results. In the comparative aspect of the two surveyed groups of patients, comparable results were obtained after undergoing surgery for an effective persistent reduction in pain. Conclusion. Total hip arthroplasty has a persistent positive effect in relation to the leveling of pain in all patients with osteoarthritis, regardless of the etiology of the disease and, in particular, the patient's body weight.